JENIS MOTIVASI DAN KEARFIAN LOKAL PETANI DALAM BERCOCOK TANAMN JAGUNG DI KELURAHAN WALI KECAMATAN WATOPUTE KABUPATEN MUNA - Sinta Sri Widyani; Dasmin Sidu; Hartina Batoa (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
This study aims to determine the types of farmer motivations in growing corn and the forms of local wisdom of farmers in growing corn. This study is motivated by the motivation of farmers and the forms of local wisdom carried out in growing corn in Wali Village which have been passed down from generation to generation from ancient times to the present. Corn is planted for various reasons by farmers in Wali Village. One of the reasons is because corn plants produce quickly which allows farmers to obtain relatively fast results and reduce the risk of losses due to factors such as weather or pest and disease attacks. In addition, because corn is also used as a staple food to replace rice by farmers in Wali Village, they see its strategic value in meeting local food needs and providing important sources of carbohydrates, proteins and fats for the local community. The diversity of nutrients contained in corn makes it an important food source in supporting the nutritional adequacy of the community, especially in areas such as Wali Village. On the other hand, as a fulfillment of the needs in corn farming, it is also supported by the climate and topography in the area so that it is very suitable for corn farming compared to other crops in general. The determination of informants in this study used a purposive technique or intentionally by taking thirty-six corn farmers. The data collection process was carried out by observation, in-depth interviews and documentation. Data analysis used descriptive analysis, namely data intended to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually or in groups. The results of the study showed that the types of farmer motivation in corn farming in Wali Village included intrinsic motivation and extrinsic motivation and the form of local wisdom of farmers in corn farming in Wali Village included tangible and intangible forms of local wisdom.